Mapping Regional Disparities in Human Development- The Case of Erstwhile Andhra Pradesh. (2016) - Kumar, Radhika P.; Prabhakaran, Priyanjali; George, Jain K.; Parambath, Saritha G.
Abstract: Census 2011 marked erstwhile Andhra Pradesh as the second largest and fifth most populous state of India housing 7% of its total population. In 2014, it was divided into the two states of Telangana and Andhra Pradesh on the basis of disparities in resource allocation. Mapping regional disparities can aid in effective policy-making at the preliminary stage of planning itself. This paper aims to study the regional disparities in human development in the case of erstwhile Andhra Pradesh through the tool of graduated colour mapping. Indicators mapped were drawn from the Andhra Pradesh Human Development Report of 2007. The studies reveal that while there is a clear case of polarized growth in the case of Hyderabad and its immediate surroundings, we also find similar trends in the Vizianagaram district, as well as in the Rayalseema region.